Mycobacterium tuberculosis cAMP Receptor Protein (Rv3676) Differs from the Escherichia coli Paradigm in Its cAMP Binding and DNA Binding Properties and Transcription Activation Properties - Stapleton, Melanie (American Society for Biochemistry and Molecular Biology, 2010)
The pathogen Mycobacterium tuberculosis produces a burst of cAMP upon infection of macrophages. Bacterial cyclic AMP receptor proteins (CRP) are transcription factors that respond to cAMP by binding at target promoters when cAMP concentrations increase. Rv3676 (CRP(Mt)) is a CRP family protein that regulates expression of genes (rpfA and whiB1) that are potentially involved in M. tuberculosis persistence and/or emergence from the dormant state. Here, the CRP(Mt) homodimer is shown to bind two molecules of cAMP (one per protomer) at noninteracting sites. Furthermore, cAMP binding by CRP(Mt) was relatively weak, entropy driven, and resulted in a relatively small enhancement in DNA binding. Tandem CRP(Mt)-binding sites (CRP1 at −58.5 and CRP2 at −37.5) were identified at the whiB1 promoter (PwhiB1). In vitro transcription reactions showed that CRP1 is an activating site and that CRP2, which was only occupied in the presence of cAMP or at high CRP(Mt) concentrations in the absence of cAMP, is a repressing site. Binding of CRP(Mt) to CRP1 was not essential for open complex formation but was required for transcription activation. Thus, these data suggest that binding of CRP(Mt) to the PwhiB1 CRP1 site activates transcription at a step after open complex formation. In contrast, high cAMP concentrations allowed occupation of both CRP1 and CRP2 sites, resulting in inhibition of open complex formation. Thus, M. tuberculosis CRP has evolved several distinct characteristics, compared with the Escherichia coli CRP paradigm, to allow it to regulate gene expression against a background of high concentrations of cAMP.